Catch Estimates and Species Composition of Recreational Fishing in Israel - Ori Frid; Tal Gavriel; Yigael Ben-Ari; Adi Weinberger; Hagar Yancovich-Shalom; Jonathan Belmaker (Fishes, 2023)
Recreational fishing is common around the Mediterranean Sea. The number of recreational fishers is growing, and they are using increasingly efficient fishing techniques. However, fisher activity is heterogeneous, both temporally and spatially, making it very difficult to determine this sector’s fishing pressure and annual yields. Therefore, estimates of annual yields and ecological effects of this fishing sector are limited. In this study, we undertook an extensive survey designed to document and quantify recreational fishing patterns across the Israeli Mediterranean shoreline. We comprehensively quantified recreational fishing using three complementary strategies: (1) ground surveys, including interviews with anglers on the coast, (2) personalized phone interviews, and (3) aerial surveys by helicopter. These methods were used to calculate annual recreational yield and to estimate species and size composition, which were then compared to the commercial fishing catch. We found that a recreational catch makes up between 10%-37% of the total annual fishing yields, which is similar to estimates from other regions of the Mediterranean. We also found that non-indigenous species are among the most common species in recreational catch and have become a significant part of local fishery yields. Recreational angling from the coast targets smaller, reef associated species compared to recreational fishers at sea. We identified 23 species common to both recreational fishing and commercial fishing, over which conflicts between fishing sectors may arise. These results can be used to more accurately manage Israeli fisheries and can provide a baseline against which to compare future changes in a region under the threats of climate change, biological invasions, and growing human pressure.